The Relative Age Effect at the Ice Hockey World Championships (IHWC) in the Years 2015–2017 - Nykodým, Jiří (J Hum Kinet, 2020)
The relative age effect (RAE) theory is based on the premise that athletes born in the first months of the calendar year have a significant probability of a higher level of physiological, morphological and psychological abilities compared to later-born athletes. The aim of our study was to verify the influence of the RAE on adult ice hockey players, specifically Ice Hockey World Championships’ (IHWC) participants in the years 2015−2017 (n = 1,200). Based on the chi-squared (χ(2)) analysis, the influence of the RAE during the 2015−2017 period could not be rejected for all observed players (χ(2) = 54.6, p < 0.01, w = 0.21) or for all the players for particular years (2015, 2016, and 2017; p < 0.01). During the monitored period (2015−2017), the RAE could not be rejected for any player’s position (forward, defender, or goaltender). Based on the effect size analysis (Cohen’s w), the strongest RAE was observed among goaltenders (w = 0.31), then forwards (w = 0.24) and finally defenders (w = 0.15). The assessment of player’s positions in particular years showed statistical significance for goaltenders only in 2015 (χ(2) = 11.3, p < 0.05). With regard to forwards, significance was confirmed for 2015 (χ(2) = 8.5, p < 0.05), 2016 (χ(2) = 15.2, p < 0.01) and 2017 (χ(2) = 14.3, p < 0.01). Therefore, the presence of the RAE could not be rejected for all these cases. The results of the research show that members of national teams in the years 2015−2017 were players who were chronologically older, which is consistent with the results of other authors addressing the RAE.